DISAIN PERBANDINGAN KARAKTERISTIK TURBIN SNAIL-LIE 4 SNAIL DAN 8 SNAIL PADA PROTOTYPE PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) - Ida Bagus Dwiki Dharma Putra; Lie Jasa; I Wayan Arta Wijaya (Program Studi Teknik Elektro UNUD, 2020)
is one of the regions with potential renewable energy sources, includinghydropower, namely the Micro Hydro Power Plant (PLTMH). The main problem with hydropoweris the flow of water that does not flow continuously throughout the year. A micro hydro that isplaced in a certain location requires a turbine in accordance with the characteristics of theexisting location. In this study, a turbine was designed to obtain a new type of Snail-Lie turbinethat accommodates all existing location parameters. In this turbine, there are variations in theform of gaps or spaces in each particular blade to trap water so that it can increase the torque,where this torque will affect the turbine output. The research method used is to findmathematical models of the Snail-Lie 4 Snail and 8 Snail turbines, make a prototype model tobe tested in the laboratory, make a real Snail-Lie turbine model for field trials. The resultsshowed that the addition of the number of snails from 4 snails to 8 snails caused the turbine'sperformance to increase, this is because the number of snails will affect the performance of theturbines, because the snail functions as a water trap so that it can be used as thrust for theturbine when it rotates. The highest output obtained is at the nozzle position 0° and the nozzleangle of 20° using a snail-lie 8 snail tubing which produces 166.9 rpm turbine rotation, 1086.8rpm generator rotation, 0.707 volt generator voltage, 0.189 watt generator power, and torqueamounting to 0.01 Nm, and an efficiency of 20.8%. The low efficiency value obtained in thesystem is 20.8% because the water entering the turbine is not comprehensive, the slip occurs inthe turbine that is coupled with the generator through the fan rope and the generator has its ownefficiency.